SUCESSIVE DIFFERENTIAL COEFFICIENTS FOR MHD VELOCITY SLIP BOUNDARY LAYER FLOW OVER A PLANE PLAQUE - Mebine, Promise (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Effects of MHD and velocity slip on boundary layer flow over a plane plaque is investigated. Similarity transformations are employed to transform the governing partial differential equations into ordinary ones, which are then solved by successive differential coeffficients (SDC) via Leibnitz-Maclaurin's method validated by numerical experiments via Runge-Kutta-Fehlberg method. The basic physically important parameters entering the problem are the Magnetic and the Velocity Slip or Fluid Sliding parameters. The results clearly represented the characteristics of the MHD velocity slip effected Blasius problem. It is seen that the SDC and numerical solutions demonstrated excellent agreements. Comparisons with available results in literature showed high degree of agreements. Typically, the velocity increases steadily and asymptotes linearly at large distances from the plate to approach the free stream mean velocity. It is observed that increase in the magnetic parameter, increases the velocity, but eliminates the linear asymptocity at the far boundary. As the magnetic parameter increases, the Lorentz force, which opposes the flow, also increases and leads to enhanced deceleration of the flow. Consequently, the magnetic parameter reduces the similarity variable boundary layer , thereby increasing the boundary layer thickness . On the other hand, increase in the fluid sliding parameter contributes to velocity jumps at the origin. The inclusion of the magnetic and velocity slip parameters modify the famous Blasius (1908) problem of boundary layer flow over a flat plate.